Supernatural. Season twelve [videorecording (DVD)] - Padalecki, Jared, 1982-; Ackles, Jensen; Collins, Misha; Sheppard, Mark, 1964- (Warner Bros. Home Entertainment, 2017)
Last season, Sam and Dean Winchester faced their greatest challenge yet: the all-powerful Darkness and sister of God, who restored their mother to life. In Season Twelve, the Winchesters must not only contend with an escaped Lucifer and the British Men of Letters (who've come to end their hunting days), but they'll also have to relearn what it is to be a family again after all these years.